Identification of transformation products during advanced oxidation of diatrizoate: Effect of water matrix and oxidation process. (15th October 2016) - Azerrad, Sara P.; Lütke Eversloh, Christian; Gilboa, Maayan; Schulz, Manoj; Ternes, Thomas; Dosoretz, Carlos G.
Abstract: Removal of micropollutants from reverse osmosis (RO) brines of wastewater desalination by oxidation processes is influenced by the scavenging capacity of brines components, resulting in the accumulation of transformation products (TPs) rather than complete mineralization. In this work the iodinated contrast media diatrizoate (DTZ) was used as model compound due to its relative resistance to oxidation. Identification of TPs was performed in ultrapure water (UPW) and RO brines applying nonthermal plasma (NTP) and UVA-TiO2 as oxidation techniques. The influence of main RO brines components in the formation and accumulation of TPs, such as chloride, bicarbonate alkalinity and humic acid, was also studied during UVA-TiO2 . DTZ oxidation pattern in UPW resulted similar in both UVA-TiO2 and NTP achieving 66 and 61% transformation, respectively. However, DTZ transformation in RO brines was markedly lower in UVA-TiO2 (9%) than in NTP (27%). These differences can be attributed to the synergic effect of RO brines components during NTP. Moreover, reactive species other than hydroxyl radical contributed to DTZ transformation, i.e., direct photolysis in UVA-TiO2 and direct photolysis + O3 in NTP accounted for 16 and 23%, respectively. DTZ transformation led to iodide formation in both oxidation techniques but it further oxidized to iodate by ozone in NTP. In total 14 transformation products were identified in UPW of which 3 were present only in UVA-TiO2 and 2 were present exclusively in NTP; 5 of the 14 TPs were absent in RO brines. Five of them were new and were denoted as TP-474A/B, TP-522, TP-586, TP-602, TP-628. TP-522 (mono-chlorinated) was elucidated only in presence of high chloride titer-synthetic water matrix in NTP, most probably formed by active chlorine species generated in situ. TPs accumulation in RO brines was markedly different in comparison to UPW. This denotes the influence of RO brines components in the formation of reactive species that could further attack DTZ/TPs and/or scavenging performed by these brine components that could limit further TPs degradation. Five plausible degradation pathways are proposed for DTZ transformation in UPW. Graphical abstract: Highlights: DTZ oxidation was tested during oxidation process by UVA-TiO2 and NTP. Effect of RO brines matrix components was more markedly in UVA-TiO2 than in NTP. 14 transformation products were elucidated of which 5 were not previously reported. Of the fourteen TPs found in UPW, five were absent in RO brines. Five plausible degradation pathways are proposed for DTZ transformation in UPW.